2016
DOI: 10.1007/s11571-016-9386-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile feedback for conveying object shape information as perceived by artificial sensing of robotic arm

Abstract: This work is a preliminary study towards developing an alternative communication channel for conveying shape information to aid in recognition of items when tactile perception is hindered. Tactile data, acquired during object exploration by sensor fitted robot arm, are processed to recognize four basic geometric shapes. Patterns representing each shape, classified from tactile data, are generated using micro-controller-driven vibration motors which vibrotactually stimulate users to convey the particular shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Biological communication modeling and systems design through neurons and networks [96], is engaging haptics to interface brain (mind) and machine, enhance motor control, and develop artificial tactile sensing using 200 Hz probes for object-shape recognition [97] to complement auditory and visual data streams for cyberphysical information flow and smart device control. As the largest organ of our body, our skin provides tactile channels that can be used for communication in a variety of taskspecific haptic interface designs [98].…”
Section: Discussionmentioning
confidence: 99%
“…Biological communication modeling and systems design through neurons and networks [96], is engaging haptics to interface brain (mind) and machine, enhance motor control, and develop artificial tactile sensing using 200 Hz probes for object-shape recognition [97] to complement auditory and visual data streams for cyberphysical information flow and smart device control. As the largest organ of our body, our skin provides tactile channels that can be used for communication in a variety of taskspecific haptic interface designs [98].…”
Section: Discussionmentioning
confidence: 99%
“…Several substitutions for sensory perception have been developed, which do not require implantable interfaces (Lundborg and Rosen, 2001 ; Visell, 2009 ; Khasnobish et al, 2016 ): Sensory substitution is a technique to provide an alternative path for necessary sensory information to the body using other sensory passages that are different from those naturally used. For instance, Kaczmarek et al ( 1991 ) revealed that hearing and vibration can serve as a substitute for touch and pressure, respectively.…”
Section: Non-invasive Methods Of Sensory Feedbackmentioning
confidence: 99%
“…However, the BCI-Utility metric is highly dependent on the system and experimental design, and thus interface-specific. The formulas derived by Dal Seno et al have been sufficient for most applications in evaluating fully-synchronous P300 spellers [ 20 ], [ 21 ], [ 22 ], [ 23 ], so only a few works have derived new BCI-Utility metric formulas for new cases [ 24 ], [ 25 ], [ 26 ], [ 27 ], [ 28 ].…”
Section: Introductionmentioning
confidence: 99%